1-Year of COVID-19 pandemic - Neiva-Sousa, Manuel (2022)
Objectives: Due to COVID-19 pandemic, social distancing policies were enacted worldwide, including by the Portuguese official authorities. However, the impact of these measures on maxillofacial trauma and fracture surgical repair remains poorly understood. The aim of this study was to evaluate and compare the incidence and aetiology of facial fractures submitted to surgical repair during 1-year of COVID-19 pandemic versus the previous 4 years, in a level III Trauma Centre located in Lisbon, Portugal. Materials and methods: All emergency episodes registered in our hospital between March 2016 and February 2021 that resulted in patient admittance for surgical treatment of facial fracture were included. Comparative analysis was performed for variables such as fracture type and aetiology. Results: Analysis showed that surgeries performed during the 1st year of COVID-19 were reduced by 37.5 %. Considering only the 75-day lockdown period at the beginning of the pandemic, reduction was even more pronounced and reached-66.7 %. Significant differences in the aetiology were also found, with physical assault and sport accidents relative frequency decreasing. Moreover, despite being systematically the second most common cause of fracture, during lockdown, fall ranked first, over physical assault. The relative frequency of nasal fractures, the most common facial fracture treated in our hospital, decreased during both the 1st year of COVID-19 and the lockdown period, while mandible fractures ranked first during lockdown. Conclusions: Our study shows that COVID-19 pandemic and enacted policies have significantly changed the epidemiology of maxillofacial trauma.